Teologi Migrasi: Kontribusi Teoritis dan Teologis terhadap Pemahaman Agama dalam Upaya Melawan Perdagangan Manusia di Nusa Tenggara Timur (NTT - Oematan, Isakh Bendris (Badan Strategi Kebijakan Hukum, 2024)
Theology of Migration represents a form of praxis that elucidates the relationship between theology (religion) and social reality, with a particular focus on migration. This relationship is characterized by intricate, intertwining, and constructive engagement. This leads to the question of whether migration theology can address the issue of migrants who eventually become involved in the criminal act of trafficking in persons (TPPO). Since 2016, NTT has been identified as a key area of concern in the context of human trafficking. Recent research on the phenomenon of human trafficking has identified a number of socio-structural issues that contribute to its prevalence, including deficiencies in education, poverty, patriarchal structures, feudalistic systems, and the scarcity of natural and human resources. The objective of this paper is to demonstrate that religion can play a significant role in the fight against TPPO in NTT. As an integral aspect of human existence, religion can serve as a foundation for efforts to provide crucial insights into the phenomenon of migration. Migration theology endeavors to reflect the phenomenon of migration in the light of public theology, thereby providing a basis for defense. This is then realized in practical actions against TPPO, with the objective of actively involving religion. In this context, migration theology will undertake a comprehensive examination of the various factors underlying the migration of people in NTT. It will then engage in interdisciplinary dialogue with the results obtained, particularly with regard to the teachings of Christianity concerning the phenomenon of migration (in terms of tradition, doctrine, the Bible, and theology). The latter can be enhanced with additional theological perspectives, particularly those pertaining to interfaith dialogue, in order to develop a comprehensive theological perspective on migration and to foster a distinctive theological approach to the migration patterns of the people of NTT. This research is grounded in a literature review employing a prosessional correlation approach, wherein Scripture, theological-dogmatic tradition, and socio-cultural human experience converge and engage in a dynamic interplay, ultimately manifesting itself in theological and practical terms.